(3Tb GdLjhH Yf CSQGQ eYGfi GdZjhH hJLdi GdeMHhH aj Cab SeG GdbdhHs - (3GdbTJGdj , eMeO Hf TYjH Hf eMeO GdMLGRj GdTYjHj GdGHTjgj,J (B1035 (3g` s
(3ChdgG (B:s
(3hHYO abO SCdfi HYV ENhGfi ef GdeMHjf Cf CYde dg fHPI dWjaI ai eYQaI MbjbI GdbdH hSYJg s
(3BNQgG (B:s
(3hdJcf gPg GdebGdI BNQ gPg GdQSGdI hGddg Gdehab ddUhGH s
(3GdfSNI HgG MhGTs
(3HChdg eWGdYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdagQSJ EHf GdfOje(B: (3L (B2 - (3U (B53s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI s
Keywords: (3GdJUha hGdBOGH GdTQYjIs